Arginyl-fructosyl-glucose, a major Maillard reaction product of red ginseng mitigates cisplatin-evoked intestinal toxicity in vivo and in vitro. Issue 21 (13th October 2022) - Liu, Wei; Zhang, Hao; Hou, Yun-yi; Hu, Rui-yi; Zhang, Jun-jie; Chen, Xuan; Wang, Shuang; Hu, Jun-nan; Wang, Zi; Li, Wei
Abstract : Cisplatin-evoked profound gastrointestinal symptomatology is one of the most common side effects of chemotherapy drugs, further causing gastrointestinal cell damage, diarrhea and vomiting. Abstract : Cisplatin-evoked profound gastrointestinal symptomatology is one of the most common side effects of chemotherapy drugs, further causing gastrointestinal cell damage, diarrhea and vomiting. Panax ginseng C. A. Meyer, a widely used medicinal and edible plant in China, shows many pharmacological activities. Nevertheless, the role of non-saponin is less known and has great potential in the treatment of severe toxic side effects related to the cisplatin treatment. The present work evaluates the efficiency of a major Maillard reaction product (MRP) of red ginseng, arginyl-fructosyl-glucose (AFG), against cisplatin-evoked intestinal toxicity in vivo and vitro, and the underlying possible mechanisms are also explored. The cisplatin-treated mice (a dose of 20 mg kg −1 for one time) showed serious intestinal mucosa damage accompanied by increased indicators of diamine oxidase (DAO) and decreased expression of tight junction proteins zonula occludens-1 (ZO-1) and occludin. Moreover, cisplatin exposure increased intestinal cell apoptosis with decreased expression of Bcl-2 and increased expression of Bax and cleaved-caspase 3/9 as well as NF-κB related proteins. Interestingly, the supplements of AFG at doses of 40 and 80 mg kg −1 day −1 for 10 days significantly ameliorated these changes. It was also demonstrated in cultured IEC-6 cells that AFG enhanced the expression levels of apoptotic proteins during cisplatin exposure and reduced the sensitivity of IEC-6 cells to cisplatin by inhibiting the activation of GSK3β and up-regulating the protein expression of β-catenin. In conclusion, AFG exerted protective effects against cisplatin-induced intestinal toxicity, at least partially by the inhibition of NF-κB-mediated apoptosis, via regulating Wnt/β-catenin signaling pathway.